Prolactin Activation of the Long Form of its Cognate Receptor Causes Increased Visceral Fat and Obesity in Males as Shown in Transgenic Mice Expressing only this Receptor Subtype - Le, J. A.; Wilson, H. M.; Shehu, A.; Devi, Y. S.; Aguilar, T.; Gibori, G. (Hormone and Metabolic Research, 2011)
To date the best defined function of prolactin (PRL) is its action on the ovary and mammary gland, although it has also been shown to have an effect on lipid metabolism. Using mice engineered to express only the long form of the prolactin receptor (PRL-RL), we demonstrate that PRL acting through PRL-RL alone causes severe adipose accumulation in visceral fat of males at 6 months of age. The increase in visceral fat accumulation is attributed to loss of adipose-derived leptin, which results in diminished lipolysis. The reduction in leptin also corresponds to decreased activation of AMP-activated protein kinase (AMPK), which further results in diminished fatty acid oxidation and increased fatty acid synthesis. Interestingly, the blunted AMPK response was only observed in adipose tissue and not in liver suggesting that this PRL mediated effect is tissue specific. A glucose tolerance study inferred that PRL-RL mice may suffer from insulin resistance or a reduction in insulin production that is not due to aberrant expression of glucose transporter 4 (Glut4). Collectively, our findings demonstrate that PRL signaling through the long form receptor causes reduced fatty acid oxidation, increased lipid storage, glucose intolerance, and obesity. These findings are of great importance towards understanding the etiology of obesity associated with hyperprolactinemia in humans as well as the role of PRL as a metabolic regulator in adipose tissue.
Keywords: prolactin; adipose; obesity; AMP-activated protein kinase